Digital technology in fixed implant prosthodontics - Joda, Tim; Ferrari, Marco; Gallucci, German O.; Wittneben, Julia‐Gabriela; Brägger, Urs (Periodontology 2000, 2017)
Digital protocols are increasingly influencing prosthodontic treatment concepts. Implant‐supported single‐unit and short‐span reconstructions will benefit mostly from the present digital trends. In these protocols, monolithic implant crowns connected to prefabricated titanium abutments, which are created based on data obtained from an intraoral scan followed by virtual design and production, without the need of a physical master cast, have to be considered in lieu of conventional manufacturing techniques for posterior implant restorations. No space for storage is needed in the complete digital workflow, and if a remake is required a replica of the original reconstruction can be produced quickly and inexpensively using rapid prototyping. The technological process is split into subtractive methods, such as milling or laser ablation, and additive processing, such as three‐dimensional printing and selective laser melting. The dimensions of the supra‐implant soft‐tissue architecture can be calculated in advance of implant placement, according to the morphologic copy, and consequently are individualized for each patient. All these technologies have to be considered before implementing new digital dental workflows in daily routine. The correct indication and application are prerequisite and crucial for the success of the overall therapy, and, finally, for a satisfied patient. This includes a teamwork approach and equally affects the clinician, the dental assistant and the technician as well. The digitization process has the potential to change the entire dental profession. The major benefits will be reduced production costs, improvement in time efficiency and fulfilment of patients’ perceptions of a modernized treatment concept.